Pengembangan Model Pembelajaran Kooperatif Berbasis Sentra untuk Meningkatkan Kecerdasan Sosial Emosional Anak - Sumiyati, Sumiyati (THUFULA, 2020)
This study examines the development of a center-based cooperative learning model to improve children's social emotional intelligence. Research uses a qualitative approach with emphasis on the quality of data in the field. An important factor that influences the success of learning is the selection of a center learning model. The results of this study indicate that the center-based cooperative learning model is one of the learning models that are considered successful. Because the center provides opportunities for children to develop their ideas. The ideas of children can be realized in the centers of the main activities which are held in collaboration with friends and teachers as facilitators. This learning raises a cooperative atmosphere that arises in each learning activity. The choice of learning model must be supported by the competencies possessed by the teacher, so that it can implement a center-based cooperative learning model properly. Teachers need to have the ability to carry out learning. This learning is also proven to be successful in improving children's social emotional abilities. These social emotional abilities can be seen from children's self-awareness, self-responsibility and others as well as pro-social aspects.  Keywords: learning models, centers, social emotional.